1992
DOI: 10.1143/jjap.31.3144
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of (PbCa)(MeNb)O3 at Microwave Frequencies

Abstract: We have investigated the dielectric properties up to microwave frequencies of ceramics represented as (Pb1-x Ca x )-(Me m Nb1-m )O3 where Me is selected from Li, Na, Mg, Zn, Ni, Co, Fe, Y, Yb, Al and Cr. High Q values and small temperature coefficients of resonant frequency were obtained in (PbCa)(Mg1/3Nb2/3)O3, (PbCa)(Ni1/3Nb2/3)O3 and (PbCa)-(Fe1/2Nb1/2)O3 with perovskite structure. These dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…[27] reported that the K value is correlated with the average ionic radius of the B-site in perovskite ceramics. In addition, Kato et al [28] suggested that a low K value results from a decrease in the movement of the ions at the Ti-site The volume of the M-site varies with both a and u, and is calculated as follows:…”
Section: Resultsmentioning
confidence: 99%
“…[27] reported that the K value is correlated with the average ionic radius of the B-site in perovskite ceramics. In addition, Kato et al [28] suggested that a low K value results from a decrease in the movement of the ions at the Ti-site The volume of the M-site varies with both a and u, and is calculated as follows:…”
Section: Resultsmentioning
confidence: 99%
“…1 The PCFN has high e r and a small temperature coefficient of relative permittivity at microwave frequencies along with a high loss tangent (tan d). 7 In order to reduce the losses and to make them suitable for these electronic devices, several attempts have been made to tailor the properties of these materials by the substitution at A-and/or B-sites. [10][11][12][13][14][15] In complex perovskites, B¢ and B¢¢ ion pairs show a variety of physical properties; 16 therefore, B-site substitution has been preferred in the present research work.…”
Section: Introductionmentioning
confidence: 99%
“…PCFN and PCFN based solid solutions are the promising materials for microwave applications [33][34][35]. Several attempts have been made to design and develop these materials by substituting various isovalence and hetrovalence elements/atoms at both A-and/or B-site [21,22,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%